You'll never seek alone: The impact of active labour market policies on finding a job - José M. Arranz; Carlos García-Serrano (Journal for Labour Market Research, 2024)
Using the administrative records of the Spanish Public Employment Service for the period 2018-2019, we analysed the impact of participation in job search assistance and training programmes on the chances of unemployed jobseekers finding employment, as well as the quality of the job obtained. Propensity score matching techniques were used to evaluate the effectiveness of these programmes. We found that participation exerted a positive and significant differential effect on the probability of transition from unemployment to employment and on the probability of finding a job of intermediate quality compared to non-participation. This positive impact was largely due to the effect of training programmes, the magnitude of which persisted even as the period elapsed between participation and exit towards employment increased, whereas job search assistance was less effective over time. The positive influence of participation appeared to be more intense for specific socioeconomic groups.
Keywords: C52; J08; J68; 330; Evaluation; Active labour market policies; Job finding; Job search assistance; Training for the unemployed